The study of rhenium pentacarbonyl complexes using single-atom chemistry in the gas phase. Issue 13 (19th March 2019) - Wang, Yang; Cao, Shiwei; Zhang, Jicai; Fan, Fangli; Yang, Jie; Haba, Hiromitsu; Komori, Yukiko; Yokokita, Takuya; Morimoto, Kouji; Kaji, Daiya; Wittwer, Yves; Eichler, Robert; et al.
Abstract : Two experiments prove Re pentacarbonyl could exist stably in the gas phase at the single-atom level. Abstract : A gas-phase chemical study of rhenium carbonyls was carried out using short-lived radioisotopes produced at a heavy-ion accelerator. The Re isotopes produced in the nuclear reactions of nat Gd( 23 Na, x n) 172–177 Re were pre-separated with a gas-filled recoil ion separator and their carbonyls were synthesized in a mixture of inert gas and carbon monoxide. Using a low temperature isothermal chromatography apparatus, the adsorption enthalpies of Re carbonyls were derived to be Δ H ads = −42 ± 2 kJ mol −1 on a Teflon® surface by fitting the external chromatograms with a Monte Carlo simulation program. A chemical yield of 25% relative to that of the transport yield for Re by a He/KCl gas-jet was achieved. The laser-ablation time-of-flight mass-spectrometric technique was employed to identify the species of Re carbonyls produced in the gas phase. The most stable species was deduced to be Re(CO)5 based on the mass-spectrometric analysis as well as quantum chemistry calculations.